Clinical Presentation of Pelvic Tuberculosis Imitating Ovarian Malignancy - Yun-Ju Huang; Lin-Hung Wei; Chang-Yao Hsieh (Elsevier, 2004)
Objective: Pelvic tuberculosis is rare, but is problematic for differential diagnosis. In this communication, we report a case series of pelvic tuberculosis clinically presenting as ovarian malignancy. Case Series: Over the past 10 years in our hospital, six cases of pelvic tuberculosis were seen. Five were thought to be ovarian malignancies, presenting either with ascites, an elevation of serum CA-125, or an adnexal tumor. Four patients underwent exploratory laparotomy and one received only peritoneoscopic biopsy. Extensive peritoneal seedings and omental thickening were discovered in all cases. Caseating granuloma on histopathologic examination was found in all of the patients. Four out of five patients received a complete course of combined anti-tuberculous treatment. All remain free of disease. Conclusion: Pelvic tuberculosis should be taken into account, especially in premenopausal women who manifest with massive ascites and adnexal tumors. Tumor markers such as CA-125 give limited information for the differential diagnosis of pelvic tuberculosis and ovarian carcinoma. We suggest exploratory laparotomy and intraoperative frozen pathology for the diagnosis of pelvic tuberculosis. New insight needs to be applied to tuberculosis.